Gesture and Sign Language in Human-Computer Interaction and Embodied Communication 9th International Gesture Workshop, GW 2011, Athens, Greece, May 25-27, 2011, Revised Selected Papers - Efthimiou, Eleni; Kouroupetroglou, Georgios; Fotinea, Stavroula-Evita.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes revised selected papers from the 9th International Gesture Workshop, GW 2011, held in Athens, Greece, in May 2011. The 24 papers presented were carefully reviewed and selected from 35 submissions. They are ordered in five sections named: human computer interaction; cognitive processes; notation systems and animation; gestures and signs: linguistic analysis and tools; and gestures and speech.
Human Computer Interaction -- Gestures in Assisted Living Environments -- Using Wiimote for 2D and 3D Pointing Tasks: Gesture Performance Evaluation -- Choosing and Modeling the Hand Gesture Database for a Natural User Interface -- User Experience of Gesture Based Interfaces: A Comparison with Traditional Interaction Methods on Pragmatic and Hedonic Qualities -- Low Cost Force-Feedback Interaction with Haptic Digital Audio Effects -- Cognitive Processes -- The Role of Spontaneous Gestures in Spatial Problem Solving -- Effects of Spectral Features of Sound on Gesture Type and Timing -- Human-Motion Saliency in Complex Scenes -- What, Why, Where and How Do Children Think? Towards a Dynamic Model of Spatial Cognition as Action -- Notation Systems and Animation A Labanotation Based Ontology for Representing Dance Movement -- ISOcat Data Categories for Signed Language Resources -- Assessing Agreement on Segmentations by Means of Staccato, the Segmentation Agreement Calculator according to Thomann -- How Do Iconic Gestures Convey Visuo-Spatial Information? Bringing Together Empirical, Theoretical, and Simulation Studies -- Thumb Modelling for the Generation of Sign Language -- Gestures and Signs: Linguistic Analysis and Tools Toward a Motor Theory of Sign Language Perception -- Analysis and Description of Blinking in French Sign Language for Automatic Generation -- Grammar/Prosody Modelling in Greek Sign Language: Towards the Definition of Built-In Sign Synthesis Rules -- Combining Two Synchronisation Methods in a Linguistic Model to Describe Sign Language -- Sign Segmentation Using Dynamics and Hand Configuration for Semi-automatic Annotation of Sign Language Corpora -- Gestures and Speech Integration of Gesture and Verbal Language: A Formal Semantics Approach -- Generating Co-speech Gestures for the Humanoid Robot NAO through BML -- Interaction between Speech and Gesture: Strategies for Pointing to Distant Objects -- Making Space for Interaction: Architects Design Dialogues -- Iconic Gestures in Face-to-Face TV Interviews.
Keywords: Computer science; Multimedia information systems; User interfaces (Computer systems).; Artificial intelligence; Computer graphics; Image processing; Pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; User Interfaces and Human Computer Interaction; Computer Imaging, Vision, Pattern Recognition and Graphics; Image Processing and Computer Vision; Pattern Recognition; Multimedia Information Systems; Electronic books